Compensating for the Zero: An Adlerian Analysis of Inferiority and Moral Construction in Black Clover - Virel Taqi Mahendra Suryoseno; Abdillah Nugroho (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This study aims to comprehensively identify the psychological factors driving Asta’s struggle to become the Wizard King in the anime Black Clover from an Adlerian perspective, and to interpret how this struggle shapes moral messages based on Nurgiyantoro's metrics. While previous studies have focused on linguistic and semiotic aspects of the series, this study provides the first dedicated psychological framework for understanding its protagonist's developmental arc. Employing a descriptive qualitative approach with content analysis, the research analyzes primary data consisting of scenes and dialogues from the anime. The findings reveal that Asta’s psychological journey begins with an absolute inferiority feeling due to being born without magic in a society that idolizes it. He counteracts this limitation by establishing a fictional finalism of becoming the Wizard King and actively striving for superiority through extreme physical training, which is fundamentally guided by a profound social interest. Furthermore, this continuous Adlerian struggle manifests as distinct moral values including extreme mental resilience, a never-give-up spirit, the dignity of hard work, courage, and altruism, transmitted through his attitudes, actions, and consequences. Ultimately, the study concludes that Asta’s narrative is a concrete illustration of healthy psychological coping mechanisms and offers significant character-building didactic values, proving the enduring relevance of classical Adlerian theory in contemporary visual media.